The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1159/000438812
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Origin, Phenotypic Effects and Diagnostic Implications of Complex Chromosome Rearrangements

Abstract: Complex chromosome rearrangements (CCRs) are currently defined as structural genome variations that involve more than 2 chromosome breaks and result in exchanges of chromosomal segments. They are thought to be extremely rare, but their detection rate is rising because of improvements in molecular cytogenetic technology. Their population frequency is also underestimated, since many CCRs may not elicit a phenotypic effect. CCRs may be the result of fork stalling and template switching, microhomology-mediated bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 260 publications
4
90
1
7
Order By: Relevance
“…In contrast to the present de novo CCR localized in a small region of chromosome 2, most constitutional CCRs involve 2 or more chromosomes [Kloosterman and Cuppen, 2013]. To date, only a few cases of CCRs involving only a single (2) none ( chromosome have been described [López-Expósito et al, 2008;Kloosterman et al, 2012;Poot and Haaf, 2015]. The CCR in our patient is responsible of the 2q37.3 deletion (2.580 Mb) and the heterogeneity of partial trisomies involving the 2q34q37.2 region.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In contrast to the present de novo CCR localized in a small region of chromosome 2, most constitutional CCRs involve 2 or more chromosomes [Kloosterman and Cuppen, 2013]. To date, only a few cases of CCRs involving only a single (2) none ( chromosome have been described [López-Expósito et al, 2008;Kloosterman et al, 2012;Poot and Haaf, 2015]. The CCR in our patient is responsible of the 2q37.3 deletion (2.580 Mb) and the heterogeneity of partial trisomies involving the 2q34q37.2 region.…”
Section: Discussioncontrasting
confidence: 59%
“…In one of the cases, the CCR involved 5 chromosomes and 5-15 breakpoints [Houge et al, 2003]; in the other case, the CCR, at the PLP1 locus, included triplication and quadruplication [Beck et al, 2015]. Recently, the review of Poot and Haaf [2015] provided some guidance as to how current molecular cytogenetic techniques can be used to resolve constitutional CCRs and to determine their respective mechanisms of origin. Array-CGH is a powerful tool to identify the breakpoints involved in complex rearrangements; however, this methodology may not be appropriate for the characterization of heterogeneous rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на большой клинический и эксперимен-тальный материал, посвященный феномену хромо-трипсиса, механизмы его возникновения и развития остаются неясными [50,74]. Поскольку подавляющее число поломок ДНК при хромотрипсисе по своей сути является микрогомологичным [45], есть все основания считать, что репарация возникших в клетке повреж-дений ДНК осуществляется путем негомологичного концевого спаривания [75,76], что успешно исполь-зуется для его выявления.…”
Section: основные механизмы хромотрипсисаunclassified
“…Thereupon, the authors isolated cell clones and confirmed in clones with aneuploidy and/ or marker chromosomes by telomere fusion PCR that telomere fusion had indeed taken place. By whole-genome sequencing clusters of genomic rearrangements, affecting one or more chromosomes and exhibiting hallmarks of chromothripsis, such as close spatial clustering, random fragment orientation and oscillating copy number states were found [Korbel and Campbell, 2013;Poot and Haaf, 2015]. Those were in particular terminal deleAll linear chromosomes are capped at their ends, the telomeres, by special telomeric repeat sequences [Riethman, 2008].…”
Section: From Telomere Crisis Via Dicentric Chromosomes To Kataegis Amentioning
confidence: 99%
“…Loss of TERT activity may cause a few rare autosomal recessive, dominant and X-linked syndromes, such as dyskeratosis congenita 1, idiopathic pulmonary fibrosis and myelodysplastic syndrome, and may be involved in ageing [Armanios and Blackburn, 2013;Vermeij et al, 2015]. Single chromosomes undergo, upon loss of their telomeric repeat sequences, breakage-fusion-bridge cycles, producing dicentric chromosomes, which may subsequently be degraded into mitotically stable dicentric supernumerary marker chromosomes [Murnane, 2012;Spittel et al, 2014;Poot and Haaf, 2015]. Products of breakage-fusionbridge cycles are rarely observed, since cell cycle checkpoints prevent their proliferation.…”
Section: From Telomere Crisis Via Dicentric Chromosomes To Kataegis Amentioning
confidence: 99%